2010
DOI: 10.4314/ajnt.v3i1.57593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peripheral Vascular Calcification and Serum Magnesium Level in a Group of Egyptian Hemodialysis Patients

Abstract: Introduction: Vascular calcification is a risk factor for cardiovascular mortality in the general population. It is highly prevalent in end stage renal disease (ESRD) patients. Low magnesium (Mg) levels have been reported to have a strong association with vascular calcification in hemodialysis (HD) patients. The aims of this study were to evaluate the prevalence of vascular calcification and its relation to serum Mg concentration in a group of Egyptian HD patients. Methods:We studied 65 stable patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…These data seem to be in accordance with previously reported in vitro and clinical studies that have already correlated lower Mg levels with vascular calcification [13,23,24], and cardiovascular mortality [25] in hemodialysis patients and also with progression to ESRD [22] as well as data from animal [26] and in vitro [27][28][29] studies stating that increased Mg levels protect against vascular calcification.…”
Section: Discussionsupporting
confidence: 92%
“…These data seem to be in accordance with previously reported in vitro and clinical studies that have already correlated lower Mg levels with vascular calcification [13,23,24], and cardiovascular mortality [25] in hemodialysis patients and also with progression to ESRD [22] as well as data from animal [26] and in vitro [27][28][29] studies stating that increased Mg levels protect against vascular calcification.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical and epidemiological studies have consistently suggested that vascular calcifications and hence arterial stiffness play an important role in the pathogenesis of cardiovascular disease and are a strong risk factor for increased morbidity and mortality in patients with end-stage renal disease (ESRD) [13]. [14] reported that vascular calcification is common in the study population and is associated with a lower serum fetuin-A level. High or sustained-normal serum fetuin-A levels may have a protective role against the development of vascular calcification in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Izawa et al [ 116 ] had described a haemodialysis patient in whom soft-tissue calci fi cation resolved after treatment with a dialysate with a high concentration of magnesium. Subsequently, other clinical studies demonstrated a clear association between low magnesium and arterial calci fi cations or other atherosclerotic lesions in dialysed renal patients [115][116][117][118][119][120][121][122][123][124] . In a number of clinical studies, a correlation of low serum magnesium with either vascular calci fi cations or carotid intima-media thickness (an index of atherosclerosis) has been demonstrated in ESRD patients.…”
Section: Arterial Calci Fi Cations Atherosclerosismentioning
confidence: 99%